A Promising Candidate: Heparin-Binding Protein Steps onto the Stage of Sepsis Prediction - Yang Yang; Guihuan Liu; Qingnan He; Jie Shen; Linyong Xu; Ping Zhu; Mingyi Zhao (Journal of Immunology Research)
Sepsis is a systemic inflammatory response syndrome caused by infection. With high morbidity and mortality of this disease, there is a need to find early effective diagnosis and assessment methods to improve the prognosis of patients. Heparin-binding protein (HBP) is a granular protein derived from polynuclear neutrophils. The biosynthetic HBP in neutrophils is rapidly released under the stimulation of bacteria, resulting in increased vascular permeability and edema. It is reasonable to speculate that the HBP in plasma may serve as a novel diagnostic marker for sepsis, bacterial skin infection, acute bacterial meningitis, leptospirosis, protozoan parasites, and even some noncommunicable diseases. It implies that in the detection and diagnosis of sepsis, it will be possible to make relevant diagnosis through this new indicator in the future. In this review, we summarize the typical biological function of HBP and its latest research progress to provide theoretical basis for clinical prediction and diagnosis of sepsis.